Reduced‐dose craniospinal irradiation for central nervous system relapsed neuroblastoma. Issue 9 (1st July 2020) - Luo, Leo Y.; Kramer, Kim; Cheung, Nai‐Kong V.; Kushner, Brian H.; Modak, Shakeel; Basu, Ellen M.; Roberts, Stephen S.; Wolden, Suzanne L.
Abstract: Purpose: In patients with high‐risk neuroblastoma, there is an increased recognition of relapse in the central nervous system (CNS). Craniospinal irradiation (CSI) has been an effective treatment but carries significant long‐term complications. It is unclear whether reducing the CSI dose from 21 to 18 Gy can achieve similar CNS tumor control. Patients and methods: A retrospective review of pediatric patients with CNS‐relapsed neuroblastoma treated with CSI and boost to parenchymal lesions between 2003 and 2019 was performed. The goal was to assess CNS control comparing 18 Gy and 21 Gy regimens. Results: Ninety‐four patients with CNS‐relapsed neuroblastoma were treated with CSI followed by intraventricular compartmental radioimmunotherapy. Median age at the time of CNS disease was 4 years (range 1‐13 years). Forty‐one patients (44%) received 21 Gy CSI prior to an institutional decision to lower the dose; 53 patients (56%) received 18 Gy CSI. Seventy‐nine patients (84%) received additional boosts. With a median follow up of 4.1 years for surviving patients, 2‐year CNS relapse‐free survival was 74% for 18 Gy group versus 77% for 21 Gy group, and 5‐year CNS relapse‐free survival was 66% for 18 Gy versus 72% for 21 Gy group, respectively ( P  = .40). Five‐year overall survival rate was 43% in 18 Gy group versus 47% in 21 Gy group ( P  = .72). Conclusion: For patients with CNS‐relapsed neuroblastoma, CNS disease control is comparable between 18 Gy and 21 Gy CSI dose regimens, in conjunction with radioimmunotherapy and CNS penetrating chemotherapy. More than 65% of the patients remain CNS disease free after 5 years. The findings support 18 Gy as the new standard CSI dose for CNS‐relapsed neuroblastoma.